BIOS-02. CLINICAL OUTCOMES OF OVER 600 PATIENTS WITH GLIOBLASTOMA TREATED AT A CANADIAN TERTIARY CENTER IN THE PAST 15 YEARS: A COMPARATIVE ANALYSIS WITH THE PIVOTAL STUPP TRIAL. (14th November 2022) - Rousseau, Julien; Desforges, Sara-Maude; Jabbour, Gilbert; Lemieux, Bernard; Lapointe, Sarah; Bélanger, Karl; Moumdjian, Robert; Cayrol, Romain; Florescu, Marie; Masucci, Giuseppina Laura; Berthelet, France; Lemieux-Blanchard, Émilie; et al.
Abstract: Glioblastoma is the most common malignant primary central nervous system tumor in adults and is associated with a poor prognosis. The benefit of adding concomitant followed by adjuvant temozolomide to radiotherapy after maximal safe resection was demonstrated by Stupp and colleagues in 2005 and has since remained the standard of care. This regimen conferred a statistically significant benefit with a 2-year survival rate of 26.5% compared to 10.4% in patients treated with radiotherapy alone. Our primary goal was to retrospectively assess the clinical outcomes of patients with glioblastoma treated at our institution over the past 15 years by comparing the overall survival (OS) and progression-free survival (PFS) from our cohort to data from the pivotal trial. Our secondary objective was to create a comprehensive database with clinical and pathological information in order to identify predictive and prognostic factors. We reviewed the clinical records of patients treated for glioblastoma from January 2005 to November 2019 at our center. We extracted data on survival and calculated OS and PFS using the Kaplan-Meier method. 617 patient charts were reviewed, out of which 17 were excluded because of missing data. The remaining 600 patients were included. Baseline demographic information was similar to that of the Stupp cohort, with the exception of a larger proportion of patients aged 50 or above (76% versus 69%, respectively). The median OS at our center was 14.3 months, 95% confidence interval [12.8-15.2], which was comparable to that of the original trial (14.6 months [13.2-16.8]). PFS was better in our cohort at 6 months (74.2% [70.7-77.7] versus 53.9% [48.1-59.6]) and 12 months (36.3% [32.5-40.2] versus 26.9% [21.8-32.1]), and comparable thereafter. Our study confirms that the data from the Stupp trial are reproducible in a Canadian academic center setting. Our database will allow us to explore potentially new predictive factors.